ANALISIS PEGELOLAAN SAMPAH DINAS LINGKUNGAN HIDUP DAN PERTANAHAN KABUPATEN KEPULAUAN SIAU TAGULANG BIARO - Melisa Putri Kakesing; Christian Bertom Pajung; Maxie Moleong (Yayasan Syalom Cipta Sumikolah, 2025)
Backgroud Analysis of Waste Management conducted by the Department of Environment and land Service (DPLH) is an important aspect in maintaining a clean and sustainable evironment.Good waste management helps reduce negative impacts on the analysis of waste management of the nenivormental and land services of he SITARO islands Regency. This study uses a qualitative method. Research informants consisted of the Head of the service, Pollution nd Environmental Damage Control Section, Waste Management Division,B3 Waste and Pollution Control, Waste Officers, residents. The results of the study concluded that the Environmental and Land Service of the SITARO Islands Regency at the stage of waste sorting, waste collection, wasteTransportation, snd waste management were not carried oud properly for the community in the context of waste management of the Envioronmental and Land Service of the SITARO Regency.it has shown its role in mnaging waste so that it can be further processed and provide benefits to the environment, but in waste transprtation it has not been carried out properly because of the lack of mobility in waste transportation, therefore the head of the Service plans to increase the mobility of waste collectors.